1998
DOI: 10.1063/1.477558
|View full text |Cite
|
Sign up to set email alerts
|

Accurate ab initio near-equilibrium potential energy and dipole moment functions of the X 2B1 and first excited A22 electronic states of OClO and OBrO

Abstract: Using highly correlated multireference configuration interaction wave functions with large correlation consistent basis sets, three-dimensional near-equilibrium potential energy functions ͑PEFs͒ have been calculated for the X 2 B 1 and first excited 2 A 2 electronic states of the atmospherically important OClO and OBrO radicals. The analytical PEFs have been used in perturbational and variational calculations of the anharmonic spectroscopic constants and vibrational spectra of both species. Excellent agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 58 publications
8
79
0
Order By: Relevance
“…[30]) with a computational grid of size 128 × 128 × 64. Peterson [27] computed the electronic ground state and the first excited state of the ClO 2 molecule in a number of points and fitted the potential energies to a polynomial. We use these potential energies.…”
Section: A Problem With Several Spatial Degrees Of Freedomexcitation mentioning
confidence: 99%
“…[30]) with a computational grid of size 128 × 128 × 64. Peterson [27] computed the electronic ground state and the first excited state of the ClO 2 molecule in a number of points and fitted the potential energies to a polynomial. We use these potential energies.…”
Section: A Problem With Several Spatial Degrees Of Freedomexcitation mentioning
confidence: 99%
“…20 Ab initio results reported by Peterson and Werner were consistent with a single minimum along the asymmetric-stretch coordinate in support of the anharmonic-coupling model. 21,22 Consensus as to the nature of the 2 A 2 surface along the asymmetric-stretch coordinate has not been achieved; however, both models predict that substantial evolution along the asymmetric-stretch coordinate occurs following photoexcitation. This prediction raises the question, does evolution along the asymmetricstretch coordinate indeed occur upon photoexcitation?…”
Section: The Excited-state Reaction Dynamics Of Oclomentioning
confidence: 99%
“…10 However, more extensive recent work has concluded that the negative (according to the sign convention adopted here) anharmonicity corrections arise from strong anharmonic coupling between symmetric and asymmetric stretching modes. 11 Again, a normal coordinate force constant scaling approach is ill-suited to capturing these effects. This is reflected in the residual error data illustrated in Figure 1(d).…”
Section: Anharmonicity Modelmentioning
confidence: 99%